Acute aortic dissection combined with cardiac tamponade in an elderly patient saved by pericardial drainage: A case report. Issue 1 (16th November 2020) - Une, Kazunobu; Hidaka, Yui; Maeda, Junji; Kinoshita, Hiroki; Kodama, Hiroshi; Sato, Katsutoshi
Abstract: Acute aortic dissection combined with cardiac tamponade is fatal. The radical treatment is an aortic replacement; however, the risk is high. We suggest conservative treatment with pericardial drainage as a treatment option in elderly patients with comorbidities. Abstract : Acute aortic dissection combined with cardiac tamponade is fatal. The radical treatment is an aortic replacement; however, the risk is high. We suggest conservative treatment with pericardial drainage as a treatment option in elderly patients with comorbidities.